Knowledge of nursing professionals about prevention of venous catheter-related bloodstream infection in a pediatric and neonatal intensive care unit - Silva, Bianca; Chinaia Junior , Mariano (Brazilian Journal of Global Health, 2023)
OBJETIVO: Identificar o conhecimento dos profissionais da equipe de enfermagem sobre a prevenção de infecção de corrente sanguínea relacionada a cateteres venosos em unidade de terapia intensiva pediátrica e neonatal. MÉTODOS: Pesquisa de campo com caráter analítico e quantitativo através de questionário com 50 profissionais da enfermagem que atuam na Unidade de Terapia intensiva neonatal e pediátrica de um hospital na zona sul de São Paulo há no mínimo três meses. RESULTADOS: Ainda que todos os participantes tenham acertado mais de 50% das questões sobre medidas de prevenção de infecção, identificou-se uma vulnerabilidade no conhecimento dos profissionais, de maneira que por menor que seja a dificuldade do profissional, pode causar dano ao paciente. CONCLUSÃO: O presente estudo tornou-se possível a identificação de lacunas no conhecimento dos profissionais da equipe de enfermagem sobre o tema proposto, sendo necessárias medidas educativas o que justifica a importância da pesquisa. DESCRITORES: Corrente Sanguínea, Infecções Transmitidas por Sangue, Cateteres, Neonatologia, Pediatria. ABSTRACT OBJECTIVE: To identify the nursing staff knowledge on venous catheters-related bloodstream infection prevention in pediatric and neonatal intensive care unit. METHODS: Quantitative and analytical field research, using a questionnaire with 50 nursing professionals working in the neonatal and pediatric intensive care unit of a hospital in the south zone of São Paulo for at least three months. RESULTS: Although all participants answered more than 50% of the questions about infection prevention measures, a vulnerability in the professionals' knowledge was identified, so that no matter how difficult it may be, it can cause harm to the patient. CONCLUSION: This study made it possible to identify gaps in the knowledge of nursing professionals about the proposed theme, requiring educational measures, which justifies the importance of this research. DESCRIPTORS: Blood Stream, Blood-borne Infections, Catheters, Neonatology, Pediatrics.